Occurrence of Red-Bloom in Fish Pond in Chitwan District, Nepal - Mandal, Ram Bhajan; Rai, Sunila; Shrestha, Madhav Kukar; Jha, Dilip Kumar; Pandit, Narayan Prasad; Rai, Shiva Kumar (Himalayan Journal of Science and Technology, 2017)
Red-bloom in fish pond has become a common problem in Nepal. In order to assess causative agents and seasonal variations of red bloom in fish pond, a study was conducted in the eastern, western and southern sites of Chitwan district from September, 2013 to June 2014. Preliminary data on occurrence and effect of red bloom were collected by visual observation and household survey of 30 randomly selected households using semi-structured questionnaire. Water quality and phytoplankton population were monitored in those ponds for four seasons, viz., autumn, winter, spring and summer. Among phytoplanktons, Euglena sanguinea was abundant in the pond water indicating the reason of red color in the pond. E. Sanguinea exhibited seasonal variation corresponding with the occurrence of red bloom in the pond. Highest density of E. Sanguinea was in summer (1628.4±70.4 number/L) which can be attributed to higher temperature and total nitrogen content of the water. Greater red bloom was observed in the southern site compared to eastern and western sites, where water was more stagnant, un-drainable and came from under-ground source.